Perencanaan Arsitektur Komputer Di Universitas Graha Nusantara Dengan Pendekatan TOGAF - Wendi, Al; Budiarti, Lela; mandopa, Andi saputra (Fakultas Teknik, Universitas Wiraraja, 2025)
- The development of information technology requires universities to have a planned, integrated computer architecture that is capable of supporting both academic and non-academic needs. The Institute for Research and Community Service (LPPM) of Graha Nusantara University (UGN) requires a computer system that can support research data management, community service activities, and integration with the university's overall information system. This study aims to design a computer architecture at LPPM UGN using the Open Group Architecture Framework (TOGAF) Architecture Development Method (ADM) framework. The research methods include literature studies, analysis of existing conditions, collection of user needs data, and design of an architectural blueprint based on the TOGAF ADM stages. The results of the study produce an architectural design that includes business architecture, information systems, and technology, equipped with a phased implementation plan and change governance mechanisms. This design is expected to improve system integration, data management efficiency, and computer network security within the LPPM UGN environment. Thus, TOGAF has proven to be an effective approach to support digital transformation in universities.